Voice modulations in german ironic speech - Scharrer, Lisa; Christmann, Ursula (Language and speech, 2011)
Previous research has shown that in different languages ironic speech is acoustically modulated compared to literal speech, and these modulations are assumed to aid the listener in the comprehension process by acting as cues that mark utterances as ironic. The present study was conducted to identify paraverbal features of German ?ironic criticism? that may possibly act as irony cues by comparing acoustic measures of ironic and literal speech. For this purpose, samples of scripted ironic and literal target utterances produced by 14 female speakers were recorded and acoustically analyzed. Results showed that in contrast to literal remarks, ironic criticism was characterized by a decreased mean fundamental frequency (F0), raised energy levels and increased vowel duration, whereas F0-contours differed only marginally between both speech types. Furthermore, we found ironic speech to be characterized by vowel hyperarticulation, an acoustic feature which has so far not been considered as a possible irony cue. Contrary to our expectations, voice modulations in ironic speech were applied independently from the availability of additional, visual irony cues. The results are discussed in light of previous findings on acoustic features of irony yielded for other languages.